DINAMIKA DEINDUSTRIALISASI INDUSTRI TEKSTIL DAN PRODUK TEKSTIL (TPT) DAN DAMPAK KEBERADAANNYA TERHADAP LINGKUNGAN KASUS DI KOTA SURAKARTA DAN KABUPATEN KARANGANYAR - , Bambang Suhardi, ST.,MT., Prof. Dr. H. Hadi Sabari Yunus, MA, DRS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development in Textile and Products of Textile (TPT) industries in Surakarta and Karanganyar city showed reduced workforce. This phenomenon is a symptom of deindustrialization. TPT industry is also considered to have polluted the environtment. The objectives of this research are: 1) observing the dynamics of deindustrialization of TPT industries, and 2) examining the environtment impacts of the presence of the TPT industry. The research approach used is the ecological approach. This research uses primary and secondary data. The data are analyzed using several methods such as descriptive analysis, multiple linear regression, location quotient, geographic information systems, noise measurement, and laboratory testing. The research results are as follows: 1) TPT industry in the city of Surakarta in the period 1997-2008 proved experienced deindustrialization. TPT industry in the city of Karanganyar not experienced deindustrialization